A survey of flaws near welds detected by side angle ultrasound examination of anhydrous ammonia nurse tanks. (September 2016) - Russell, A.M.; Becker, A.T.; Chumbley, L.S.; Enyart, D.A.; Bowersox, B.L.; Hanigan, T.W.; Labbe, J.L.; Moran, J.S.; Spicher, E.L.; Zhong, L.
Abstract: A sample of 532 anhydrous ammonia nurse tanks with manufacture dates ranging from the 1950's to 2011 were examined during 2012 by side angle ultrasound to measure the locations, sizes, and orientations of flaw indications. The indications were most frequently located on the head side of the head-to-shell welds and oriented perpendicular to the weld line in the welds' heat affected zones. On average newer tanks had more indications than older tanks. Tanks that had been given a post-weld stress relief anneal had markedly fewer indications. Graphical abstract: Highlights: Ultrasound inspection of 532 used nurse tanks determined the location, size, and orientation of their cracks and other flaws. A total of 3326 indications were detected. Indications most often lay on the head side of the head-to-shell welds, oriented perpendicular to the weld line in the HAZ. On average newer tanks had more indications than older tanks. Post-weld stress relief annealed tanks had far fewer indications than did tanks retaining residual stresses from welding.